2020
DOI: 10.1108/oir-04-2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of e-government implementation at the local level: an empirical model

Abstract: PurposeThe empirical research of e-government at the local level has been the subject of many studies in the last two decades. The evidence collected by those studies constitutes a relevant opportunity toward the development of a theory of local e-government implementation. However, several synthesis efforts are needed before such a theory can be developed. The purpose of this article is to contribute to that endeavor by proposing an empirical model of the determinants of e-government implementation by local g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 93 publications
1
29
0
2
Order By: Relevance
“…Although size and demography are not relevant for adoption, they contribute to explain the number of functionalities offered through mobile applications by the local governments that adopt them. Thus, there seems to be a difference between determinants of adoption and determinants of use, which might be the consequence of the different phases of e-government implementation that may be at stake, namely adoption and institutionalization [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although size and demography are not relevant for adoption, they contribute to explain the number of functionalities offered through mobile applications by the local governments that adopt them. Thus, there seems to be a difference between determinants of adoption and determinants of use, which might be the consequence of the different phases of e-government implementation that may be at stake, namely adoption and institutionalization [14].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic literature review on the determinants of local e-government implementation has found that there is "a common set of determinants that explains local e-government implementation in general, and three other sets of determinants that contribute to differentiate each one of three e-government dimensions: e-transparency, e-participation, and e-services" [14]. The common set of determinants includes determinants associated with the internal characteristics of the local government (size, management capacity, financial capacity, technical capacity, leadership, organization form and culture, and previous experience), and determinants associated with the territorial jurisdiction of the local government (demography, socioeconomic dynamism, and Internet use).…”
Section: Related Work and Hypotheses 21 Determinants Of Local E-gover...mentioning
confidence: 99%
See 2 more Smart Citations
“…Andrade & Batalha (2017); Barros (2015); Batalha (2017); Cunha et al, (2015); Dias (2020); ITM (2017); Leston-Bandeira (2016); Olsen (2018); Rodríguez et al, (2019); Sangki (2017); Shane (2006); Valbruzzi (2015).…”
Section: Akutsu (2005);mentioning
confidence: 99%